Different Approaches to requesting Consent for Routine data linkage in Neonatal follow-up (ACORN): protocol for a 2×2 factorial randomised trial - Jane E Harding; Barry Milne; Jenny Rogers; Greg Gamble; Jane Marie Alsweiler; Christopher McKinlay; Gavin Brown; Aakash Bajirao Rajay; Caroline Anne Crowther; Nike Franke; Trecia Wouldes (BMJ Open)
Introduction Routinely collected data can be linked to research data to create a rich dataset and inform practice. However, consent is normally required to link identifiable data. Reported rates of consent to data linkage for children ranged from 21% to 96%, but no studies have investigated different approaches to seeking consent for data linkage for school-age children.Methods and analysis The Approaches to Consent for Routine Data Linkage in Neonatal Follow-up (ACORN) trial is a 2×2 factorial randomised trial to assess whether, for children who participated in neonatal randomised trials (pre-hypoglycaemia Prevention with Oral Dextrose Gel (hPOD), hPOD and The Impact of Protein Intravenous Nutrition on Development in Extremely Low Birth Weight Babies (ProVIDe)) and are approached to participate in an in-person assessment at 6–7 years of age, parental consent to data linkage is higher if consent is sought (1) after the in-person assessment (delayed) or concurrently and (2) for health and education data combined or separately. The primary outcomes will be rates of consent to linkage of (1) either health or education data and (2) both health and education data. A pilot study indicates the potentially available cohort size of 2110 (80% follow-up of the neonatal trial cohorts) would be adequate to detect an absolute difference of 6%–5%–4% from a baseline consent rate of 70%–85%–90%, respectively (2-tailed alpha 0.05, 90% power). With at least 1136 participants, the ACORN trial would have 90% power to detect an absolute difference of 5% in the primary outcome for each factor, assuming a consent rate of 90% in the control groups and alpha 0.05. Data are categorical and will be presented as number and per cent. The effects of factors will be tested using generalised linear models and presented as ORs and 95% CIs.Ethics and dissemination Ethics approval by the New Zealand Health and Disability Ethics Committee (19/STH/202). Dissemination will be via peer-reviewed publications, scientific meetings, educational sessions and public fora.Trial registration number ACTRN12621000571875 (Australian New Zealand Clinical Trials Registry).